Influence of landscape-variation in geochemistry on taxonomic and functional composition of microbial mat communities in the McMurdo Dry Valleys, Antarctica - Risteca, Paul Joseph (Virginia Tech, 2023)
Microbial communities play critical roles in biogeochemical cycles of aquatic and terrestrial ecosystems, but studies of soil microbial communities have been limited by the diversity and complexity found in most ecosystems. Here we report on work investigating the functional diversity of microbial mat and underlying soil communities in the McMurdo Dry Valleys of Antarctica across a gradient of phosphorus availability on glacial tills of distinct age and mineral composition in Taylor Valley, Antarctica. Microbial mat and soil DNA were extracted and sequenced on an Illumina NextSeq500 in a 150 bp paired end format. Raw sequences were uploaded to the MG-RAST server for processing and annotation. Community taxonomic and functional annotation were determined using the RefSeq and SEED Subsystem databases, respectively. The results revealed significant variation in microbial mat community taxonomic composition between the two tills, strongly associated with visual assessment of mat morphology, e.g., "black" and "orange" mats, and soil N:P ratios. The underlying soil microbial communities did not exhibit significant differences in diversity between the two tills, but community composition varied significantly across gradients of soil chemistry, particularly extractable-phosphate content even within tills. The relative abundance of biogeochemistry-relevant pathways determined from the SEED database varied amongst soil microbial communities between the two tills. For example, microbial mat communities exhibited significant variation in the relative abundance of key nitrogen and phosphorus metabolism associated genes strongly associated with the underlying soil N:P. These results suggest that spatial variation in geochemistry influences the distribution and activity of microbial mats, but that the microbial mats themselves also exert a significant homogenizing effect on the underlying soil communities and some of the key biogeochemical processes they facilitate. Master of Science Microbial communities play critical ...